A 4-week consumption of light or dark roast unfiltered (Turkish) coffee affects cardiovascular risk parameters of homocysteine and cholesterol concentrations in healthy subjects: a randomized crossover clinical trial.: The effects of unfiltered (Turkish) coffee consumption on cardiovascular risk parameters. - Eren, Fatma Hulyam; Besler, Halit Tanju (Progress in Nutrition, 2019)
Background/aim: The aim of this study is to investigate the impact of boiled, unfiltered (Turkish) coffee consumption on the plasma cardiovascular risk parameters of healthy subjects. The study also explores whether two unfiltered coffee beverages that differ in content due to varying degrees of roasting will affect cardiovascular biomarkers differently. Methods: In this crossover intervention study, healthy, nonsmoking, habitual Turkish coffee drinkers (n=28) were randomized to consume at least 3 cups of Light (LR) or Dark (DR) roast Turkish coffee brews per day for 4 weeks after a washout period (WO) of 2 weeks. Subsequent to each coffee abstinence period, both groups received the alternative intervention. After the first WO and the coffee intervention periods, anthropometric measures, blood pressure, heart rate and 10 biochemical parameters were collected and dietary records were completed. Results: The consumption of 3 ≥ cups Turkish coffee/day for 4 weeks, compared with the results after 2 weeks of coffee abstinence, led to a significant increase in homocysteine levels of habitual Turkish coffee drinkers in both coffee interventions (p<0.01). Anthropometric measurements, fasting blood glucose, blood pressure and heart rate did not change during the coffee consumption phase in either of the Turkish coffee groups. Both roasts increased concentrations of serum lipids compared to WO. However, only DR Turkish coffee intake significantly increased total cholesterol levels (p<0.05). Conclusion: Moderate amounts of LR or DR Turkish coffee consumption for 4 weeks, although differing in content, largely show similar biological effects as demonstrated by the tested cardiovascular biomarkers.